2022
DOI: 10.1007/s10840-022-01204-1
|View full text |Cite
|
Sign up to set email alerts
|

Procedural time reduction associated with active esophageal cooling during pulmonary vein isolation

Abstract: Background Active esophageal cooling is increasingly utilized as an alternative to luminal esophageal temperature (LET) monitoring for protection against thermal injury during pulmonary vein isolation (PVI) when treating atrial fibrillation (AF). Published data demonstrate the efficacy of active cooling in reducing thermal injury, but impacts on procedural efficiency are not as well characterized. LET monitoring compels pauses in ablation due to heat stacking and temperature overheating alarms th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…[21][22][23] Active esophageal cooling using a dedicated esophageal cooling device is a newer technique that has shown benefits in preclinical studies, mathematical modeling, and clinical studies. [24][25][26][27][28][29][30][31][32][33][34] An international multicenter randomized controlled trial is currently underway (NCT04577859), but this study relies on the surrogate endpoint of endoscopically detected esophageal lesion (EDEL) reduction. Because an event rate of <1% requires an extremely large sample size, no study to date has evaluated the effectiveness of any strategy in reducing AEFs.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Active esophageal cooling using a dedicated esophageal cooling device is a newer technique that has shown benefits in preclinical studies, mathematical modeling, and clinical studies. [24][25][26][27][28][29][30][31][32][33][34] An international multicenter randomized controlled trial is currently underway (NCT04577859), but this study relies on the surrogate endpoint of endoscopically detected esophageal lesion (EDEL) reduction. Because an event rate of <1% requires an extremely large sample size, no study to date has evaluated the effectiveness of any strategy in reducing AEFs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the tools aiming to increase safety of RFCA regarding esophageal injuries, an active cooling tool (ensoETM, Attune Medical, Chicago, IL, USA) has been tested in single center and multicenter trials showing better safety and outcomes, and shorter duration procedure over a control group, with the limitations of requiring general anesthesia [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Different methods have been proposed for this purpose which broadly may be considered ‘reactive’ (apply in response to an elevated oesophageal temperature) or ‘proactive’ cooling (pre-emptively cool prior to any risk of thermal injury). 35 Reduced procedure time, 36 fluoroscopy, 37 and overall cost 38 and no reduction in ablation efficacy, efficiency, and safety 39 were some of the benefits highlighted for dedicated active cooling devices. In turn, a recent systematic review and meta-analysis found that oesophageal cooling did not reduce the overall risk of any oesophageal injury compared to control.…”
Section: Strategies To Target the Spb By Percutaneous Radiofrequency ...mentioning
confidence: 99%